E0334 Investigation for effects of sotalol combined with propafenone to treat paediatric atrial tachycardia. (17th November 2010) - Xiaomei, Li; Yan, Zhang; Yi, Zhang; Min, Bao; Ping, Lu
Abstract : Objects: To evaluate the efficacy, safety, selection and combination program of anti-arrhythmic drugs to treat paediatric atrial tachycardia. Methods: 42 children (male 19, female 23, age 7 days–14 years) diagnosed of atrial tachycardia were treated by oral anti-arrhythmic drugs. 24 h holter monitoring and wireless remote realtime monitoring system were used to evaluate the efficacy. Cardiac function was evaluated by echocardiogram. Side effects of drugs were closely detected during the whole process. Results: 21 cases were firstly treated by single sotalol, none were completely cured, 20 were partially cured (95.2%), 1 was ineffective (4.8%). 41 cases were finally treated by sotalol plus propafenone, 30 were completely cured (73.2%), 9 were partially cured (21.9%) and 2 were ineffective (4.9%). The effective dose of sotalol was 5.4–5.7 mg/kg.d, and the effective dose of propafenone was 9–10.5 mg/kg.d. 5 cases of incessant atrial tachycardia complicated by tachycardiomyopathy (5/17, 29.4%) were treated by amiodarone plus metroprolol, 1 was completely cured and the others' cardiac function were obviously improved after treatment although none of them were completely cured, they all reverted to sotalol plus propafenone while cardiac function became nearly normal. Injury of thyroid function happened in 3 cases after taking oral amiodarone for 3–8 months and all recovered during 1 month after withdrawing the drug. During the 1–14 months of follow up for the 31 cases completely cured, only 1 case of intermittent atrial tachycardia recurred at No.8 month after withdrawing the drug. Conclusion: 1. Sotalol is a safe and effective anti-arrhythmic drug which can be used to treat paediatric atrial tachycardia, effective dose is 4.89–5.71 mg/kg.d; 2. Combination use of sotalol plus propafenone is obviously more effective than single use of sotalol with satisfactory safety; 3. Combination use of sotalol plus propafenone is safer and more effective than combination use of amiodarone plus metroprolol. 4. Amiodarone might lead to thyroid function injury, and can be used as transitional drug for patients diagnosed of tachycardiomyopathy.